2023
DOI: 10.1126/sciadv.ade7236
|View full text |Cite
|
Sign up to set email alerts
|

Ribonucleotide reductase regulatory subunit M2 drives glioblastoma TMZ resistance through modulation of dNTP production

Abstract: During therapy, adaptations driven by cellular plasticity are partly responsible for driving the inevitable recurrence of glioblastoma (GBM). To investigate plasticity-induced adaptation during standard-of-care chemotherapy temozolomide (TMZ), we performed in vivo single-cell RNA sequencing in patient-derived xenograft (PDX) tumors of GBM before, during, and after therapy. Comparing single-cell transcriptomic patterns identified distinct cellular populations present during TMZ therapy. Of interest was the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 87 publications
(131 reference statements)
1
8
0
Order By: Relevance
“…This is in good agreement with the data on the severe delay in colony formation and reduced survival of wild-type yeast under the conditions of 4-NQO action [21,22]. Similarly, in mammals, various modes of transcriptional repression or targeting RRM2 result in the suppression of tumor growth, including GBM [44,59,60]. RNR catalyzes the synthesis of dNTP by a radical mechanism [24], which can be counteracted by the formation of reactive oxygen species.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is in good agreement with the data on the severe delay in colony formation and reduced survival of wild-type yeast under the conditions of 4-NQO action [21,22]. Similarly, in mammals, various modes of transcriptional repression or targeting RRM2 result in the suppression of tumor growth, including GBM [44,59,60]. RNR catalyzes the synthesis of dNTP by a radical mechanism [24], which can be counteracted by the formation of reactive oxygen species.…”
Section: Discussionsupporting
confidence: 90%
“…So, high antitumor activity of the combination of bortezomib and 4-hydroxysalicylanilide (a specific inhibitor of the RRM2 subunit of RNR) was shown against MM cell lines, including primary cells obtained from a patient with MM refractory to bortezomib [41]. Recent work shows that drugs that target RNR or inhibit its expression sensitize GBM to standard therapy [42][43][44]. To our knowledge, RNR inhibitors in combination with proteasome inhibitors have not yet been investigated for GBM treatment [12].…”
Section: Introductionmentioning
confidence: 99%
“…One of the co-down-regulated proteins identified in the LUC7L3-knockdown group was ribonucleotide reductase subunit M2 (RRM2), which had been reported to contribute to the progression of multiple cancers [27,28] and serve as a potential therapeutic target. More specifically, several studies have suggested that the overexpression of RRM2 was involved in the development of acquired resistance to chemotherapeutic agents such as gemcitabine, temozolomide, and so on [29][30][31].…”
Section: Luc7l3 Co-down-regulated Protein Rrm2 Is Correlated With Pro...mentioning
confidence: 99%
“…As the composition of the TME has been more fully elucidated with research studies looking into the functional consequences of interaction with these surrounding cells have begun to illuminate a dynamic cellular crosstalk between GBM itself and its TME. Studies examining GBM and its complex TME have uncovered critical insights including wide immunosuppression ( 29 , 77 80 ), integration with neuronal firing ( 81 84 ), hijacking of angiogenesis ( 85 89 ), changes in cellular metabolism ( 29 , 90 , 91 ), and disruption of normal ph. and oxygen levels ( 29 , 92 ).…”
Section: Glioblastoma Tumor Heterogeneity and Microenvironmentmentioning
confidence: 99%